Answer:
Step-by-step explanation:
Given that,
Mass of the heavier car m_1 = 1750 kg
Mass of the lighter car m_2 = 1350 kg
The speed of the lighter car just after collision can be represented as follows
![m_1u_1+m_2u_2=m_1v_1+m_2v_2\\\\v_2=(m_1u_1+m_2u_2-m_1v_1)/(m_2)](https://img.qammunity.org/2021/formulas/physics/college/d3u36lyr88wp74r2yww9tqogh9gq4zxny9.png)
![v_2=((1850)(1.4)+(1450)(-1.10)-(1850)(0.250))/(1450) \\\\=(2590+(-1595)-(462.5))/(1450) \\\\=(2590-1595-462.5)/(1450) \\\\=(532.5)/(1450)\\\\=0.367m/s](https://img.qammunity.org/2021/formulas/physics/college/ropu5vwreig4wfgcffyuid4cp7nv2ykqsx.png)
b) the change in the combined kinetic energy of the two-car system during this collision
![\Delta K.E=((1)/(2) m_1v_1^2+(1)/(2) m_2v_2^2)-((1)/(2) m_1u_1^2+(1)/(2) m_2u_2^2)\\\\=(1)/(2) (m_1(v_1^2-u_1^2)+m_2(v_2^2-u_2^2))](https://img.qammunity.org/2021/formulas/physics/college/ahnb4gqague84fr7ox4tywlxp3ugakoh53.png)
substitute the value in the equation above
![=(1)/(2) (1850((0.250)^2-(1.4)^2)+(1450((0.3670)^2-(-1.10)^2)\\\\=(1)/(2)(11850(0.0625-1.96)+(1450(0.1347)-(1.21))\\\\= (1)/(2)(11850(-1.8975))+(1450(-1.0753))\\\\=(1)/(2) (-3510.375+(-1559.185)\\\\=(1)/(2) (-5069.56)\\\\=-2534.78J](https://img.qammunity.org/2021/formulas/physics/college/dpi90h6qb6it9j655k29smyczxwotarvcl.png)
Hence, the change in combine kinetic energy is -2534.78J